2014
DOI: 10.1080/14786435.2014.885138
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening at nanoscaled coherent twin boundary in f.c.c. metals

Abstract: This paper analyses slip transfer at the boundary of nanoscaled growth twins in face-centred cubic (f.c.c.) metals for strengthening mechanism. The required stress for slip transfer, i.e. inter-twin flow stress, is obtained in a simple expression in terms of stacking fault energy and/or twin boundary (TB) energy, constriction energy and activation volume. For nanotwinned Al, Cu and Ni, inter-twin flow stress versus twin thickness remarkably shows Hall-Petch relationship. The Hall-Petch slope is rationalized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Equation (5) is in agreement with the 1/d linear relationship observed in [15,16]. If a pile-up of dislocations against the BSF occurs, the second term on the right side of Equation (1) is replaced by À3:5094 ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi d= sin h p sb r 3=2 À r 3=2 0 [18,19]. A similar derivation leads to following tensile flow stress,…”
Section: Modelsupporting
confidence: 71%
See 1 more Smart Citation
“…Equation (5) is in agreement with the 1/d linear relationship observed in [15,16]. If a pile-up of dislocations against the BSF occurs, the second term on the right side of Equation (1) is replaced by À3:5094 ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi d= sin h p sb r 3=2 À r 3=2 0 [18,19]. A similar derivation leads to following tensile flow stress,…”
Section: Modelsupporting
confidence: 71%
“…The left end and right end of the loop are pined to the grain boundary where the 〈c + a〉 dislocation is emitted into the first nanospace. From above, the maximum size of the loop within a nanospace is d= sin h. An activation methodology similar to that in the step (1) appears in the recent study of dislocation transmission across twin boundary in nano-twinned FCC metals [18,19]; a loop growth scheme similar to that used in the step (2) was employed in the study of intra-granular dislocation emitted from grain boundaries of nano-grained FCC metals [20][21][22][23].…”
Section: Modelmentioning
confidence: 99%
“…3 GBs are of particular importance because they readily manifest in medium to low stacking fault energy materials either through annealing or mechanical twinning [5][6][7]. The presence of the low energy coherent 3 interface can lead to enhanced material properties (such as strength [8][9][10], cracking resistance [6,7,11], and corrosion resistance [12]). Grain boundary engineering (GBE) emerged as a technique to optimize thermomechanical processing routes that enhance properties by increasing the fraction of 3 and other special GB types [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The twin boundary increases the work hardening rate by acting as an obstacle for gliding dislocations [75]. Together, slip transfer at the boundary of nanoscale growth twins in FCC structures also provides the strengthening mechanism and ductility enhancement [76]. It has been demonstrated that the twinning mechanism can simultaneously maintain high strength and ductility of the material.…”
Section: Influencing Factors Of Ni-based Alloy Fatigue Behaviormentioning
confidence: 99%